Laitteet pilveen - vai pilvi laitteisiin? Keskustelunavauksia teollisuuden ja yhteiskunnan digialustojen uusista kehitystrendeistä; Machines in a Cloud – or a Cloud in Machines? Emerging New Trends of the Digital Platforms in Industry and Society - Juri Mattila; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2015)
– In the beginning of the 1990's, various fragmented information networks of the Internet were combined into one integrated network of systems. As a result, the commercial utilization of the Internet boomed, creating completely new business models and economic structures in the process. A similar reaction is now anticipated from the digitalization of industry and society at large. However, the big question is, how can all the separately structured, isolated systems be fused into one seamless network of systems? So far the problem has mainly been addressed from the stand-point of centralized and decentralized system architectures. Our analysis shows, however, that completely new and innovative technological approaches, such as block chain technology, are emerging to address this problem. These new distributed architecture solutions may completely revolutionize the anticipated structures and business models of the digitalization currently in progress, as they allow machines to autonomously share much more than just data, e.g. computational capacity, storage space or even electric power. As a result, understanding digitalization in its full capacity requires a systems approach and new kind of higher-level thinking on the scale of a network of systems.
Keywords: L14; L15; L86; L96; O33; 330; Digitalization; Industrial Internet; Platforms; Block chain; Internetportal; Computernetz; Netzwerkökonomik